2019
DOI: 10.15419/bmrat.v6i11.572
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of Ginger Zingiber officinale Roscoe by Soxhlet method induces apoptosis in human hepatocellular carcinoma cell line

Abstract: Introduction: Ginger has had a long history of use in healthcare in Asian countries, including Vietnam. Internationally, there have been a few studies done to assess the anticancer activity and potency of ginger. In this study, we investigated the activity (cytotoxicity) of various ginger root extracts that were produced by different preparation methods on human hepatocellular carcinoma cell line (HepG2 cell line). Methods: Ginger (Zingiber officinale Roscoe) root extract were extracted from the fresh ginger r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These results may be due to the higher molecular weight compounds of released molecules during boiling of hot water extract and to the compounds identified by HPLC with anticancer activity. These results were in an agreement with Nguyen et al [64] and it's may be used in a form of tablets in the treatment of a wide range of other cancers, including lung, bladder, cervical, various GL cancers (gastric, pancreatic, liver, colorectal) and ovarian cancers which may be also in an agreement with Marrelli et al [43] as well as Prasad and Tyagi [65] due to its higher antiradical activity and it may be used in the form of medication to capture free radicals once it enters the body. It was shown that ginger exhibited an important role in cancer prevention by activating and inactivating various molecular pathways as reported by Rahmani et al [66].…”
Section: Anticancer Activitysupporting
confidence: 94%
“…These results may be due to the higher molecular weight compounds of released molecules during boiling of hot water extract and to the compounds identified by HPLC with anticancer activity. These results were in an agreement with Nguyen et al [64] and it's may be used in a form of tablets in the treatment of a wide range of other cancers, including lung, bladder, cervical, various GL cancers (gastric, pancreatic, liver, colorectal) and ovarian cancers which may be also in an agreement with Marrelli et al [43] as well as Prasad and Tyagi [65] due to its higher antiradical activity and it may be used in the form of medication to capture free radicals once it enters the body. It was shown that ginger exhibited an important role in cancer prevention by activating and inactivating various molecular pathways as reported by Rahmani et al [66].…”
Section: Anticancer Activitysupporting
confidence: 94%
“…The extract obtained with the US and AM methods presented significantly lower antioxidant activity (p < 0.05) than the M, R1, R2, and R3 methods, due to shorter exposure time (40 min) and heat stress [ 14 ]. Moreover, according to Nguyen et al [ 29 ], cavitation extraction is not strong enough to break the cell walls and release substances with antioxidant capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Extracts were evaporated under vacuum to dryness and stored in dried bottles at 4°C. 18 Total Flavonoid Content One millilitre of the Simplicia sample was dissolved in 10 mL water and filtered. The filtrate is put into a test tube.…”
Section: Red Ginger Preparationmentioning
confidence: 99%